2014
DOI: 10.1002/acr.22194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Adult‐Onset Still's Disease Presenting With Erosive Arthritis: Association With Low Levels of Ferritin and Interleukin‐18

Abstract: Objective. Adult-onset Still's disease (AOSD) is a clinical entity with a heterogeneous etiology. We have encountered patients with AOSD who had severe polyarthritis and who fulfilled the classification criteria for rheumatoid arthritis (RA); however, most patients with AOSD typically exhibit mild arthritis. In this study, we proposed 2 clinical subsets of AOSD and investigated the clinically significant characteristics of the 2 subtypes. Methods. We retrospectively analyzed 71 consecutive patients with AOSD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
57
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 14 publications
8
57
0
9
Order By: Relevance
“…Patients with severe systemic inflammatory disorders (non-RA subtype) presented with high IL-18 levels, whereas those that developed severe arthritis (RA subtype) presented with low IL-18 levels [54]. The present study findings were consistent with those earlier findings and indicate that s-JIA and AOSD might be pathogenically identical.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with severe systemic inflammatory disorders (non-RA subtype) presented with high IL-18 levels, whereas those that developed severe arthritis (RA subtype) presented with low IL-18 levels [54]. The present study findings were consistent with those earlier findings and indicate that s-JIA and AOSD might be pathogenically identical.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a recent study reported the existence of two subgroups of patients with AOSD that were based on serum IL-18 levels [54]. Patients with severe systemic inflammatory disorders (non-RA subtype) presented with high IL-18 levels, whereas those that developed severe arthritis (RA subtype) presented with low IL-18 levels [54].…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 and serum ferritin levels correlate with disease activity in AOSD. 15,17 Rheumatoid factor and ANA are found negative in 93% and 92% of cases respectively.…”
Section: Discussionmentioning
confidence: 96%
“…We read with great interest the article by Ichida et al published recently in Arthritis Care & Research regarding the clinical manifestations of a large cohort of patients with adult-onset Still's disease (AOSD) (1). We fully agree with the authors, and we would like to make a brief comment on both the possibility of erosive arthritis and the need for reliable clinical predictors of outcome to treat arthritis aggressively as soon as possible.…”
mentioning
confidence: 78%